1996
DOI: 10.1111/j.2042-7158.1996.tb05903.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enzyme Inhibitors and Insulin Concentration on Transepithelial Transport of Insulin in Rats

Abstract: The objective of this study was to determine whether transepithelial transport of insulin can be improved by enzyme inhibitors and whether insulin concentration affects its ileal absorption. Ussing chambers and radioimmunoassay were used to study insulin transport across the rat ileum, and circular dichroic spectra were used to determine whether insulin aggregated at high concentrations. Inhibitors that inhibit insulin-degrading enzyme, including N-ethylmaleimide, 1,10-phenanthroline and p-chloromercuribenzoat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…The P app of phenol red across the duodenum, jejunum, and ileum were the 4.04 × 10 −6 , 4.54 × 10 −6 , 5.20 × 10 −6 cm/s, respectively. These data were in accordance with those obtained from the Ussing chambers (Bai & Chang, 1996), but lower than those using the everted gut sac technique (Schilling & Mitra, 1990).…”
Section: Regions Of Ratssupporting
confidence: 85%
See 1 more Smart Citation
“…The P app of phenol red across the duodenum, jejunum, and ileum were the 4.04 × 10 −6 , 4.54 × 10 −6 , 5.20 × 10 −6 cm/s, respectively. These data were in accordance with those obtained from the Ussing chambers (Bai & Chang, 1996), but lower than those using the everted gut sac technique (Schilling & Mitra, 1990).…”
Section: Regions Of Ratssupporting
confidence: 85%
“…When the intestinal mucosal cells were destroyed, and aqueous pores in the mucosa would open up, hydrophilic molecules could more easily pass through the enlarged intercellular junctions. Such methods as the constant of transepithelial electrical resistance, accumulation of [ 3 H]-D-glucose, appearance of lactate dehydrogenase and permeability of phenol red were used to determine whether the membranes remained intact throughout the experiments (Bai & Chang, 1996). Table 1 summarizes the permeability experiment of phenol red using the Valia-Chien chambers.…”
Section: Regions Of Ratsmentioning
confidence: 99%
“…This implies that insulin, which was directly introduced into the cytosol by the FL membrane fusion, was strongly degraded by the cytosolic IDE. PCMB, a sulfhydryl-modifying agent, has been used to inhibit the degradation of insulin by IDE in various tissue cytoplasms (15,16). In the present study, no absorptionenhancing effect was observed following insulin solution coadministration of PCMB and the simple liposomes loaded with both insulin and PCMB together.…”
Section: Discussioncontrasting
confidence: 56%
“…Regarding the permeation of insulin into the intestinal epithelium, Bai and Chang (15,16) reported that insulin was highly degraded by IDE in the intestinal cytoplasm, and it potentially limits the transepithelial transport of insulin. In this study, we found that the coencapsulation of PCMB as the IDE inhibitor further increased FL's enhancement effect of insulin colonic absorption (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation